Kesepian di Masa Pandemi Covid-19: Peran Welas Diri sebagai Prediktor - Wahyu Eka Febriliyani; Mochammad Sa’id (Flourishing Journal, 2023)
AbstractThis study aims to determine whether self-compassion is a predictor of loneliness in students in Malang City due to the COVID-19 pandemic. This research is a correlational-quantitative research. The population in this study were students, with a convenience sampling technique of sampling. The research subjects in this study amounted to 67 students in the city of Malang. The data collection method used 2 questionnaires, namely the R-UCLA Loneliness Scale Version 3 to measure loneliness and the Self-Compassion Scale (SWD) to measure self-compassion. This study uses simple linear regression data analysis. The results of this study indicate that self-compassion is a significant predictor of loneliness in students in Malang City due to the COVID-19 pandemic (p=0,000 < 0,05) and contribute 16% to the loneliness (R2=0,16). Thus, it can be concluded that the higher the level of self-compassion an individual has, the lower the level of loneliness he feels. This research recommends the importance of developing self-compassion in individuals to reduce feelings of loneliness due to the COVID-19 pandemic situation. AbstrakPenelitian ini bertujuan untuk mengetahui apakah welas diri merupakan prediktor dari kesepian pada mahasiswa di Kota Malang akibat pandemi COVID-19. Penelitian ini merupakan penelitian kuantitatif korelasional. Populasi pada penelitian ini adalah mahasiswa, dengan teknik sampling convenience sampling. Subjek penelitian pada penelitian ini berjumlah 67 mahasiswa di Kota Malang. Metode pengambilan data menggunakan 2 kuesioner yaitu R-UCLA Loneliness Scale Version 3 untuk mengukur kesepian dan Skala Welas Diri (SWD) untuk mengukur welas diri. Penelitian ini menggunakan analisis data regresi linier sederhana. Hasil dari penelitian ini menunjukkan bahwa welas diri merupakan prediktor yang signifikan dari kesepian pada mahasiswa di Kota Malang akibat pandemi COVID-19 (p=0,000 < 0,05) dan berkontribusi sebesar 16% (R2=0,16). Dengan demikian, dapat disimpulkan bahwa semakin tinggi tingkat welas diri yang dimiliki individu, maka tingkat kesepian yang ia rasakan akan semakin rendah. Penelitian ini merekomendasikan pentingnya mengembangkan welas diri pada diri individu untuk mengurangi rasa kesepian akibat situasi pandemi COVID-19.